2017
DOI: 10.1016/j.ijscr.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Combination of hydroxyapatite, platelet rich fibrin and amnion membrane as a novel therapeutic option in regenerative periapical endodontic surgery: Case series

Abstract: HighlightsOur article was an attempt to focus on combined benefits of Bio-Gen mix®, PRF and amnion membrane to provide a viable regenerative option in periapical surgery.To the best of our knowledge, there has been no evidence related to the application of a human placental membrane in periapical surgery. Our presented case reports provide an insight into this novel therapeutic option.The presented case reports confirm that the amnion membrane combined with bone graft and PRF have enhanced the healing outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
12
0
3
Order By: Relevance
“…CBCT, already well established in the literature, is a fundamental tool for the diagnosis and treatment planning [ [1] , [2] , [3] , [15] , [16] , [17] , [18] , [19] ]. In the present study, three-dimensional evaluation was essential for determining the complexity of the treatment, based on the location and extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT, already well established in the literature, is a fundamental tool for the diagnosis and treatment planning [ [1] , [2] , [3] , [15] , [16] , [17] , [18] , [19] ]. In the present study, three-dimensional evaluation was essential for determining the complexity of the treatment, based on the location and extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of a series of cases has emphasized that periapical surgery should be considered the last resort in endodontics to effectively deal with periapical lesions that result from pulp necrosis. The study showed that different extraradicular infections were associated with persistent exuding symptoms, leading to endodontic failure, and were successfully treated only by periradicular surgery [ 3 , 18 ]. Unfortunately, in our study, bacterial culture was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the augment in width of keratinized gingiva with AM was found in the treatment of gingival recession, though not as effective as connective tissue graft (CTG) [ 59 , 60 ]. A clinical study confirmed the effectiveness of AM in the regenerative periapical endodontic surgery combined with HA and PRF to enhance clinical outcomes with decreased postoperative discomfort [ 61 ]. Amnion-chorion membranes were also used in alveolar ridge preservation and maxillary sinus membrane repair [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the usefulness of amniotic membrane in regenerative periapical endodontic surgery was shown when it was combined with bone graft and platelet‐rich fibrin (PRF). Such combination enhanced the radiographic healing outcome and decreased post‐operative discomfort in patients suffering from radicular cysts …”
Section: New and Unusual Applications Of Amniotic Membrane In The Woumentioning
confidence: 99%
“…Such combination enhanced the radiographic healing outcome and decreased post-operative discomfort in patients suffering from radicular cysts. 109 There are also some reports about protective effects of amniotic membrane proteins (AMPs) against hypoxiainduced injuries of cardiomiocytes, which was proven on the H9c2 rat cell line pre-treated with AMPs and subjected to 24 hours hypoxia. This procedure caused nuclear factor erythroid-2-related factor 2 (Nrf2) a hemeoxygenase 1 (HO-1) expression upregulation with concomitant downregulation of inflammatory cascaderelated proteins levels.…”
Section: New and Unusual Applications Of Amniotic Membrane In The Wmentioning
confidence: 99%